2018
DOI: 10.1302/1863-2548.12.180132
|View full text |Cite
|
Sign up to set email alerts
|

Poorer radiological outcome after delayed diagnosis and treatment in human position in Fettweis plaster cast in 93 unstable hip joints type D, III and IV according to Graf

Abstract: PurposeIn this study the course of unstable hips after successful treatment with Fettweis plaster of Paris (POP) is examined. Special focus will be given to age at beginning of treatment and initial hip type.MethodsThe development of 93 unstable hips treated between November 2001 and April 2015 was examined. Inclusion criteria were: 1) unstable hips with successful treatment with Fettweis POP; 2) presence of two pelvic radiographs (12 to 24 months and 24 to 48 months). We analyzed: 1) the initial ultrasound hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 45 publications
3
9
0
Order By: Relevance
“…In our study, failure occurred more often in patients that were primarily treated elsewhere and were significantly older upon presentation at our institution. This is in accordance with another study that described the critical time for initial treatment to be 8 weeks of age at the most for optimal results [23]. Therefore, it has been shown that early detection of DDHs through a general screening and early treatment are preventive for a large proportion of subsequent extensive hip surgeries [24].…”
Section: Discussionsupporting
confidence: 88%
“…In our study, failure occurred more often in patients that were primarily treated elsewhere and were significantly older upon presentation at our institution. This is in accordance with another study that described the critical time for initial treatment to be 8 weeks of age at the most for optimal results [23]. Therefore, it has been shown that early detection of DDHs through a general screening and early treatment are preventive for a large proportion of subsequent extensive hip surgeries [24].…”
Section: Discussionsupporting
confidence: 88%
“…The authors recommend long-term follow-up of even the successfully treated cases to detect deterioration following initial normal radiographs. 16 However, one study, which included infants with dislocated irreducible (D/I) 59 hips, reported 56.3% rate of treatment success with Pavlik harness. They added that treatment was successful until 4 months, and no correlation between treatment success and treatment initiation age was found.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis and proper treatment affect the prognosis of DDH. 2,3,9,16,17 However, the optimal time of the treatment to achieve success is not clear. The common opinion is that starting the treatment before 7 weeks of age has a positive effect on the treatment duration and success.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations